Determinan Pengelolaan Keuangan Daerah : Sistem Pengendalian Internal Sebagai Pemoderasi - Salsabila, Aina Thusamma; Suhartini, Dwi (Universitas Gorontalo, 2023)
This research aims to analyze the responses of government officials in villages or urban districts regarding transparency in local financial management moderated by the internal control system. The study was conducted in villages and urban districts in the Sidoarjo District, with a sample of 42 respondents, including Village/Urban District Heads, Village/Urban District Secretaries, and Treasurers from each village and urban district. This research is quantitative in nature, and the analysis technique used is Partial Least Square (PLS) with the assistance of WarpPLS 8.0 software. The findings indicate that transparency has a positive impact on local financial management. However, the internal control system cannot strengthen the relationship between transparency and local financial management.